THE PRODUCE FRESHNESS MONITORING SYSTEM USING RFID WITH OXYGEN AND CO2 DEVICE - Mannobjonov Boburbek Zokirjon o‘g‘li; Abdulatipov Oyatillo Alisher o‘g‘li; Isaqjonova Muqaddasoy Ismonali qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This composition proffers an oxygen and co2 absorption monitoring transaction for healthiness administration supported on old-fashioned wireless oftenness determination (RFID). healthiness buoy be checkered by indefinite constituents including humidity, temperature, oxygen, and copy dioxide. This composition focuses on oxygen and copy dioxide. The concentrations of these cardinal gases are accompanying to healthiness and influence the food. We application a device for monitoring these gases and combine the device with an RFID tag. The RFID transaction is to some degree easy to manage. With this composed system, we estimated the healthiness of vegetables. The produce has to some degree abbreviated consequence availableness period. When we invest in the vegetable, we deprivation to evaluation the healthiness criteria. on the other hand thither is no much a transaction that buoy evaluation the healthiness of vegetables, so general public dispassionate contemplate visually. If the produce goes bey the coming to an end date, general public testament communicate it away, so it occasions brobdingnagian wastefulness of almighty dollar and hawthorn intimidation customers’ health. thither testament be requisite trustworthy healthiness monitoring transaction for both purchasers and salesperson to save almighty dollar and health.